Investigating Vitamin D Awareness, Supplementation Practices, and Perceived Infertility Risk in Derna and Tobruk: A Cross-Sectional Study Integrating Pharmacy and Gynaecology Perspectives - Akrim, Taweda; Elhemiedy , Rehab Muhamed; Mohamed , Mostafa (Sharwes Scientific Journal, 2026)
Infertility is an increasing public health concern in Libya, intensified by the high prevalence of vitamin D insufficiency and related behavioural gaps among women of reproductive age. Although international evidence highlights associations between vitamin D insufficiency, ovulatory dysfunction, implantation failure, and polycystic ovary syndrome, region-specific research in North Africa remains limited. This cross-sectional study investigated the association between vitamin D awareness, supplementation practices, and self-reported infertility experiences among 1,000 women in Derna and Tobruk between March 2024 and May 2025, with emphasis on pharmacy and gynaecological practices. Data were collected through structured questionnaires measuring demographic characteristics, vitamin D awareness, infertility experiences, and professional practices, and were analysed using SPSS v29 with Pearson’s correlation, independent t-tests, and multiple regression. Results demonstrated that women recognised the role of vitamin D in reproductive health, yet regular supplementation and dietary intake were limited. A significant association was observed between lower vitamin D awareness and practices and higher self-reported infertility experiences (r = 0.42, OR = 1.53, p < 0.001). Pharmacists contributed more to supplement provision, while gynaecologists prioritised diagnostic testing. Systemic barriers such as cost, limited laboratory facilities, and weak professional collaboration strongly influenced infertility perceptions. Findings reflect reported perceptions and practices rather than biochemical measurement of serum vitamin D levels, underscoring the need for clearer clinical guidelines, affordable screening, and enhanced cooperation between pharmacists and gynaecologists to strengthen reproductive health care in eastern Libya.